2013
DOI: 10.1038/nature11807
|View full text |Cite
|
Sign up to set email alerts
|

Negligible immunogenicity of terminally differentiated cells derived from induced pluripotent or embryonic stem cells

Abstract: The advantages of using induced pluripotent stem cells (iPSCs) instead of embryonic stem (ES) cells in regenerative medicine centre around circumventing concerns about the ethics of using ES cells and the likelihood of immune rejection of ES-cell-derived tissues. However, partial reprogramming and genetic instabilities in iPSCs could elicit immune responses in transplant recipients even when iPSC-derived differentiated cells are transplanted. iPSCs are first differentiated into specific types of cells in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
366
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 457 publications
(389 citation statements)
references
References 37 publications
10
366
4
2
Order By: Relevance
“…However, in contrast to this general assumption, one recent study has used the inbred C57BL/ 6 (B6) mouse strain to demonstrate that cells differentiated from the B6 iPSCs within teratomas can be immunogenic in the syngeneic B6 recipient mice, raising concerns about the immunogenicity of iPSCs. 10 In support of this notion, and also relying on the B6 inbred mouse strain, Abe and colleagues 11 reported in Nature recently that cardiomyocytes differentiated from B6 iPSCs in vitro are highly immunogenic when transplanted into B6 mice. In the same report, however, the authors found that B6 iPSC-derived skin tissue obtained from chimeric mice generated by injecting B6 iPSCs into B6 blastocyts have negligible immunogenicity and are completely immune tolerated by B6 recipients.…”
Section: The Immunogenicity Of Induced Pluripotent Stem Cells (Ipsc)-mentioning
confidence: 97%
See 3 more Smart Citations
“…However, in contrast to this general assumption, one recent study has used the inbred C57BL/ 6 (B6) mouse strain to demonstrate that cells differentiated from the B6 iPSCs within teratomas can be immunogenic in the syngeneic B6 recipient mice, raising concerns about the immunogenicity of iPSCs. 10 In support of this notion, and also relying on the B6 inbred mouse strain, Abe and colleagues 11 reported in Nature recently that cardiomyocytes differentiated from B6 iPSCs in vitro are highly immunogenic when transplanted into B6 mice. In the same report, however, the authors found that B6 iPSC-derived skin tissue obtained from chimeric mice generated by injecting B6 iPSCs into B6 blastocyts have negligible immunogenicity and are completely immune tolerated by B6 recipients.…”
Section: The Immunogenicity Of Induced Pluripotent Stem Cells (Ipsc)-mentioning
confidence: 97%
“…In the same report, however, the authors found that B6 iPSC-derived skin tissue obtained from chimeric mice generated by injecting B6 iPSCs into B6 blastocyts have negligible immunogenicity and are completely immune tolerated by B6 recipients. 11 …”
Section: The Immunogenicity Of Induced Pluripotent Stem Cells (Ipsc)-mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, several studies provided evidence to support a different point of view regarding the immunogenicity of iPSCs. [42][43][44] While the above-mentioned study by Zhao et al 41 only used a single line of syngeneic ESCs, Araki et al 43 tested seven iPSC and five embryonic stem cell lines to verify that no pronounced differences in immunogenicity existed between the teratomas formed by iPSCs and ESCs. In fact, the disparities between iPSC-or ESC-derived clones perhaps deserve more attention than the differences between these two pluripotent stem cells.…”
mentioning
confidence: 99%